study Of Optical Properties Of Copper-Doped Cds Thin Films (Baghdad Science Journal, 2004)
Thin films of CdS:Cu were deposited onto glass substrate temperature 400 °c. The optieal properties have been studied for Cds doped with (1,3, 8) wt% of Cu before and after Gamma irradiation. It was found that the irradiation caused an ( Frenkel defects) where the atom is displaced from its original site leaving vacancy and forming on interstitial atom. It was found the irradiation caused an absorption edge shifting towards long wavelength as a result of the increasing of Cu concentration.